To write the History of Theater: between oral history, personal archives, and documentation centers (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article aimed to establish connections between oral history and personal archives, with the goal of proposing a research methodology that integrates the various documentary collections related to the history of theater. The research conducted for the dissertation Na Ciranda da Memória: Maria Helena Lopes — Narratives on Teaching Career, Passion, and Theater Education at UFRGS (1967–1994)provided examples of the use of historical sources in writing the history of theater. Furthermore, the study highlighted the importance of documentation centers dedicated to the study of Brazilian theater history.
Keywords: oral history; memory; personal archive; theater collection